The use of biochar to reduce nitrogen and potassium leaching from soil cultivated with maize - W Widowati; A Asnah; W H Utomo (Journal of Degraded and Mining Lands Management, 2014)
Nutrient leaching is often a problem especially in tropical areas with soil fertility constraints. This study aims to reveal the effect of biochars on leaching and uptake of nitrogen and potassium from degraded soils cultivated with maize. Each of three types of biochar originated from rice husk, wood, and coconut shell, was applied to the soil placed in PVC tube at four rates (0,15, 30, and 45 t/ha). Maize was then planted in each pot. All pots received urea (135 kg N/ha), SP 36 (36 kg P2O5/ha), and KCl (110 kg K2O/ha). Twelve treatments (three biochars and four application rates) were arranged in a factorial randomized block design with three replicates. Results of the study showed interaction effects of biochar materials and biochar rates on nitrate leaching (except on day 1 to 30) and potassium, N uptake, and plant growth. On day 1-30, leaching of nitrate and potassium was reduced by biochar application. The lowest nitrate leaching was observed at rate of 45 t /ha of wood biochar, while application of 45 t/ ha coconut shell biochar resulted in the highest K leaching. Beside, wood biochar resulted in a similar nitrate leaching with that of coconut shell biochars, but nitrate leaching increased with increasing rate of biochar chaff on 30-60 HST. All biochar materials yielded a similar potassium leaching at all rates. Application of 45 t /ha biochar husk resulted in the best maize growth.